PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING (STUDI KASUS DI PT. MANDALA MULTI FINANCE, TBK CABANG LUBUKLINGGAU - Azhar, Rudi; Sari, Tri Agriana (Jurnal Media Ekonomi (JURMEK), 2024)
The problem in this research is product quality, where there is still a lack of product innovation, product attractiveness, there is still a lack of information on the characteristic features and the impression of the quality of the products being marketed. Then the quality of service, there is still a lack of reliability and responsiveness in serving the wishes of consumers. Purchasing decisions, there is still a lack of conveying information about prices, there is still a lack of strategy in marketing and consumer doubts regarding the accuracy of purchasing decisions. Furthermore, consumer satisfaction, service to consumers has not been maximized, there is still a lack of consumer comments on products, and there is still a lack of attention to products in promoting sales. This research was conducted to determine the effect of product quality and service quality on purchasing decisions with consumer satisfaction as an intervening variable (Case Study at PT. Mandala Multi Finance, Tbk Lubuklinggau Branch). In this study, a four-item variable questionnaire method was used, namely Product Quality (X1), Service Quality (X2), Purchase Decision (Y) and Consumer Satisfaction (I). The data analysis technique used is Multiple Linear Regression Analysis, Coefficient of Determination (R2), and FTest. From the results of the Multiple Regression Analysis, the equation Ŷ = 4.754+0.101 X1+0.823 X2 is obtained. Furthermore, from the analysis, the value of Rsquare (R2) is 0.918 or 91.8%. This value gives the understanding that Product Quality (X1) and Service Quality (X2) contribute 91.8% to the Purchase Decision (Y). While the remaining 8.2% is influenced by other variables that are not included in this study. Based on the results of the Anova calculation (Ftest), it can be seen that the Fcount value is 219.193 with a significant level of 0.000 while Ftable with α = 5% and (n-k-1) or (42-2-1) = 39. And the numerator (k-2 ) is 3.238. Fcount (219.193) > Ftable (3.238), meaning that Ho is rejected and Ha is accepted. This shows that there is a significant influence between Product Quality and Service Quality on Purchasing Decisions.